124P A phase I study of percutaneous oncolytic rose bengal disodium for metastatic uveal melanoma patients with hepatic metastases: A single-center cohort summary. (15th December 2019) - Patel, S; Carter, B W; Balmes, G; Rider, H; Joseph, J; Zobniw, C; Trinh, V; Anderson, J; Sheth, R; Murthy, R; Wachter, E A
Abstract: Background: Rose bengal disodium (PV-10) is a small molecule oncolytic immunotherapy in clinical development for treatment of solid tumors. When administered by intralesional injection, PV-10 can produce an immunogenic cell death that may induce a T-cell mediated immune response against treatment-refractory and immunologically-cold tumors. Given this mechanism of action, we investigated treatment of metastatic uveal melanoma with percutaneous hepatic PV-10. Methods: PV-10-LC-01 (NCT00986661) is an open-label phase I basket study evaluating the safety, tolerability, and preliminary efficacy of intralesional PV-10 in patients with solid tumors metastatic to the liver. Percutaneous injections of PV-10 are administered to one or more designated hepatic tumor(s) with a maximum sum of diameters £4.9 cm. Response assessments using 2D EASL criteria are performed at Day 28, then every 3 months. Patients with additional injectable tumors may receive further PV-10 after Day 28. Eligible patients may receive standard of care checkpoint blockade immunotherapy during treatment with PV-10. Results: In a single-center cohort of uveal melanoma patients with hepatic metastases, to date, the study has screened 15 patients with metastatic uveal melanoma; eleven patients have been consented, enrolled, and received at least one PV-10 treatment cycle; five have received a second treatment with intralesional PV-10 for a total of 18 injected hepatic tumors. Three patients have received PV-10 with initiation of standard of care checkpoint blockade. One patient was on immunotherapy prior to PV-10 treatment. In 11 injected tumors with response assessment, the objective response rate has been 36%. Toxicities have been self-limiting and consistent with established patterns, including photosensitivity, pink urine, and transaminitis that resolved in < 7 days. Conclusion: Percutaneous PV-10 exhibited acceptable safety and tolerability with encouraging evidence of activity in injected lesions. Updated enrollment as well as safety and efficacy data of the uveal melanoma cohort will be presented at the meeting. Clinical trial identification: NCT00986661. Legal entity responsible for the study: Provectus. Funding: Provectus. Disclosure: S. Patel: Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Cardinal Health; Advisory / Consultancy: Castle Biosciences; Leadership role, Data Safety Monitoring Board Chair: Immunocore; Advisory / Consultancy: Incyte; Honoraria (self): Merck; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Provectus; Leadership role, Research grant / Funding (institution), Data Safety Monitoring Board chair: Reata. E.A. Wachter: Shareholder / Stockholder / Stock options, Full / Part-time employment: Provectus. All other authors have declared no conflicts of interest.